Osteoarticular infection caused by Talaromyces Marneffei and Salmonella in a person living with HIV: a case report - Lele Yu; Binhai Zhang; Jinchuan Shi; Mengyan Wang; Hu Wan (BMC Infectious Diseases, 2023)
Abstract Introduction Talaromycosis is a common invasive fungal disease in patients with HIV. However, its association with bone destruction is unusual in AIDS patients with talaromycosis. Case Presentation This report covers the case of a 38-year-old male AIDS patient coinfected with Talaromyces marneffei and Salmonella. The case, which involved bone destruction, was identified via metagenomic next-generation sequencing (mNGS). Following treatment with a combination of amphotericin B and piperacillin-tazobactam, the patient’s elbow motion noticeably improved. Imaging findings revealed that the progression of bony destruction had halted. Conclusion Bone damage due to Talaromyces marneffei infection is infrequent in HIV-positive patients. Therefore, healthcare professionals must be vigilant for potential bone lesions associated with this type of infection. Prompt diagnosis and antimicrobial treatment are crucial.